The link between English foreign language teacher’s professional identity and their critical thinking that leads to teacher’s success in the Chinese context: Leaders motivational language as a moderator - Ding, Fangfang; Liu, Xingyu; Amin Abdalla, Alaa; Latif Khan, Muhammad; Akram, Fouzia (Frontiers in Psychology, 2022)
The purpose of this study is to examine the link between employee’s professional identity and their success via mediating role of critical thinking. Further, we examined the interaction of employee’s professional commitment and leader’s motivational language via critical thinking on employee success. We collected data from Chinese MNC’s by using time lagged study design. We used hierarchical linear regression for direct hypotheses and Hayes PROCESS model’s for mediation, moderation, and mediation moderation analysis. The results show that there is positive relation between employee’s professional identity and employee’s success. Further, critical thinking mediates the link between professional identity and employee success. The results of the moderated mediation analysis show that critical thinking mediated the interaction of employee’s professional identity and leader’s motivational language on employee’s success..